Sleep and Cognition in Children with Fetal Alcohol Spectrum Disorders (FASD) and Children with Autism Spectrum Disorders (ASD) - Rabya Mughal (Brain Sciences, 2020)
Children with Fetal Alcohol Spectrum Disorders (FASD) and Autism Spectrum Disorders (ASD) experience significantly higher rates of sleep disturbances than their typically developing peers. However, little is known about the association between sleep and the cognitive phenotype in these clinical populations. Structural damage affecting cortical and subcortical connectivity occurs as a result of prenatal alcohol exposure in children with FASD, whilst it is believed an abundance of short-range connectivity explains the phenotypic manifestations of childhood ASD. These underlying neural structural and connectivity differences manifest as cognitive patterns, with some shared and some unique characteristics between FASD and ASD. This is the first study to examine sleep and its association with cognition in individuals with FASD, and to compare sleep in individuals with FASD and ASD. We assessed children aged 6–12 years with a diagnosis of FASD (n = 29), ASD (n = 21), and Typically Developing (TD) children (n = 46) using actigraphy (CamNTech Actiwatch 8), digit span tests of working memory (Weschler Intelligence Scale), tests of nonverbal mental age (MA; Ravens Standard Progressive Matrices), receptive vocabulary (British Picture Vocabulary Scale), and a choice reaction time (CRT) task. Children with FASD and ASD presented with significantly shorter total sleep duration, lower sleep efficiency, and more nocturnal wakings than their TD peers. Sleep was significantly associated with scores on the cognitive tests in all three groups. Our findings support the growing body of work asserting that sleep is significant to cognitive functioning in these neurodevelopmental conditions; however, more research is needed to determine cause and effect.